Screening and Health Behaviors among Persons Diagnosed with Familial Adenomatous Polyposis and Their Relatives. (29th July 2012) - James, Aimee S.; Chisholm, Phillip; Wolin, Kathleen Y.; Baxter, Melanie; Kaphingst, Kimberly; Davidson, Nicholas O.
Abstract : Familial Adenomatous Polyposis (FAP) is a rare autosomal dominantly inherited colorectal cancer syndrome. Individuals with FAP often undergo colectomy and are recommended to follow several surveillance protocols. Biological relatives of persons with FAP may also be at risk and thus should undergo genetic counseling. Screening adherence, genetic testing, and other health behaviors among individuals with FAP and their relatives are not well characterized. We conducted a cross-sectional self-report survey with individuals who have FAP (n = 35 ) and their biological relatives (n = 15 ). Respondents were recruited through a cancer center registry for inherited colon cancers. Most relatives had undergone colon cancer screening; 40% had undergone genetic testing. One fifth of respondents with FAP had not undergone an upper endoscopy, contrary to usual recommendations. Cigarette smoking rates were above average and were higher among FAP respondents. Use of vitamin supplements was fairly common, more so among those with FAP. Although most people had been screened, there are areas for improvement, notably for upper endoscopy among individuals with FAP and genetic testing among family members. Several other health-risk behaviors and health concerns other than FAP were identified. Further research into factors contributing to screening rates and other health behaviors in this high-risk population is warranted.